1996
DOI: 10.1177/016264349601300202
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Assistive Technology Applications in Schools and Recommendations for Practice

Abstract: The Analysis of Technology Assistance for Children (ATAC) project was undertaken in recognition of the severe limit in information on current practices in field applications of assistive technology. Specifically, the ATAC project focused on investigating three problem areas: (1) the status of assistive technology in educational and related settings with school-age children with disabilities; (2) the benefits and barriers associated with using assistive technology for these youngsters; and (3) the effects of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 7 publications
2
72
0
Order By: Relevance
“…Furthermore, two different purposes appeared when the aims of the interventions of ICT use in the studies were analysed: to compensate for the students' difficulties and to practise with the help of the ICT to increase functional capacity. In both cases ICT has been used as ATD, which has been studied for many years in children with motor impairments (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two different purposes appeared when the aims of the interventions of ICT use in the studies were analysed: to compensate for the students' difficulties and to practise with the help of the ICT to increase functional capacity. In both cases ICT has been used as ATD, which has been studied for many years in children with motor impairments (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…A 1996 survey of general special education teachers in Tennessee, Kentucky and Indiana showed that 41 % of special educators lack adequate skills to use assistive technology in the classroom (Derer, Polsgrove, & Rieth, 1996). A survey of special education teachers in Kentucky indicated that few teachers feel prepared to provide AT services to students (Bauder, 1999).…”
Section: Curriculum Access For Students With Visual Impairmentsmentioning
confidence: 99%
“…The review found that factors statistically related to the extent assistive technology use by students with visual impairments have been discussed but not been thoroughly studied (Abner & Lahm, 2002;Alves, et al, 2009;Bauder, 1999;Derer, et al, 1996;Edwards & Lewis, 1998;Kapperman, et al, 2002;Kelly, 2008;Maushak, et al, 2001;Parker, et al, 1990;D. W. Smith & Kelley, 2007).…”
Section: Literature Review Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, no one can deny that the inclusion of students in the university and the school, can no longer disregard the use of ICT technologies, (Derer, 1996) and in particular the so called Web 2.0 technologies. These technologies, however, more and more forcefully pervades our daily life; terms once reserved only to insiders as Information and Communication Technology (ICT), have now entered into common parlance, to show how their use has become pervasive and it represents, however, a valuable opportunity for anyone experience a difficulty or disability, temporary or permanent situation.…”
Section: Introductionmentioning
confidence: 99%